The role of intellectual capital on innovation: Evidence from Hungarian SMEs - Rideg, András (2023)
This study investigates the relationship between intellectual capital components and innovation on a sample of 1243 Hungarian small and medium sized enterprises (SMEs) drawn from the Global Competitiveness Project (GCP). The results of the logistic regressions reveal a significantly positive effect of structural capital and relational capital on innovation, whereas the impact of human capital is not significant. The results show the importance for entrepreneurs of strengthening intellectual capital in order to increase SMEs innovation, and advise policymakers on how to mobilize support schemes for the renewal of SMEs with low individual but high collective innovation potential. Instead of examining large enterprises and startups, the novelty of the study relies on the analysis of the connections between intellectual capital components and innovation in the context of mature Hungarian SMEs.